2007
DOI: 10.1016/j.vaccine.2007.05.052
|View full text |Cite
|
Sign up to set email alerts
|

DNA–VLP prime–boost intra-nasal immunization induces cellular and humoral anti-HIV-1 systemic and mucosal immunity with cross-clade neutralizing activity

Abstract: The immune response to HIV-1 Virus-Like Particles (VLPs), presenting a clade A Ugandan gp120, has been evaluated in a mouse model by intranasal (i.n.) administration by a VLP+VLP homologous or a DNA+VLP heterologous prime-boost immunization protocol, including a HIV-1 DNA gp160/rev plasmid. Furthermore, the effect of the Eurocine lipidbased mucosal L3 adjuvant on the VLP immunogenicity has been assessed as well.The designed heterologous protocol is able to increase the env-specific humoral and cellular immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…rBCG vaccines have been shown to efficiently prime the immune response to the heterologous antigen in recombinant adenovirus, recombinant poxvirus, and protein prime-boost combinations (24,26,27,30,57,58). We (27,44,52) and others (59) have previously shown that a Gag VLP boost, used in heterologous prime-boost modality, is a (62). Our data illustrate that rBCGpan-Gag, on its own, is immunogenic and can achieve a 100% response rate after the second vaccination in a nonhuman primate model.…”
Section: Discussionsupporting
confidence: 56%
“…rBCG vaccines have been shown to efficiently prime the immune response to the heterologous antigen in recombinant adenovirus, recombinant poxvirus, and protein prime-boost combinations (24,26,27,30,57,58). We (27,44,52) and others (59) have previously shown that a Gag VLP boost, used in heterologous prime-boost modality, is a (62). Our data illustrate that rBCGpan-Gag, on its own, is immunogenic and can achieve a 100% response rate after the second vaccination in a nonhuman primate model.…”
Section: Discussionsupporting
confidence: 56%
“…We have previously reported that baculovirus-expressed HIV-VLP A s, which display gp120 derived from a Ugandan HIV-1 isolate of the subtype A, are strongly immunogenic in BALB/c mice, inducing HIV-1-specific CD4 ϩ and CD8 ϩ T-cell responses as well as cross-clade neutralizing antibodies at systemic and mucosal sites (9,11,13). We have also shown that these HIV-VLPs are able to induce maturation of ex vivogenerated immature human MDDCs, resulting in the expression of surface maturation markers and the increased production of Th1 and Th2 cytokines, and this observation can be confirmed on unselected PBMCs (1, 10).…”
Section: Discussionmentioning
confidence: 99%
“…These HIV-VLP A s induce HIV-1-specific CD4 ϩ and CD8 ϩ T-cell responses and crossclade neutralizing antibodies in immunized BALB/c mice (11). Moreover, the intraperitoneal and intranasal administration of HIV-VLP A s in mice induces antibody responses at systemic and mucosal (vaginal and intestinal) levels (9,13).…”
mentioning
confidence: 99%
“…However, the effectiveness of mucosal immunization often relies upon coadministration of appropriate adjuvants that can initiate and support the transition from innate to adaptive immunity (recently reviewed in reference 20). In addition to adjuvants, particulate antigens (e.g., virus-like particles [VLPs]) have been shown to be advantageous for intranasal immunization, given that they efficiently target antigen-presenting cells (APCs) and facilitate the induction of potent immune responses (7,9,10,11,16,18,31,34,41,43,44). However, several vaccine concepts have been evaluated in nonhuman primates (NHPs) by intranasal administration with inconsistent immunogenicity results, probably related to the different vaccination strategy (3,17,24,26,27,29).…”
mentioning
confidence: 99%
“…Elicitation of immune response at systemic as well as mucosal (vaginal and intestinal) levels has been previously evaluated in mice by intraperitoneal as well as intranasal administration (7,8,11). In particular, the mucosal immunogenicity of such HIV-VLPs has been evaluated by comparing a homologous (VLP ϩ VLP) and a heterologous (DNA ϩ VLP) prime-boost strategy by intranasal administration, in an adjuvant formulation (7).…”
mentioning
confidence: 99%